The identity of undergraduate public affairs education: Opportunities and challenges. (2nd January 2018) - Mitchell, Jerry
ABSTRACT: Undergraduate public affairs education is an established part of American higher education. The purpose of this article is to describe the current structure of public affairs undergraduate education, the opportunities for developing degree programs in the context of modern thought about higher education and citizenship; and the continuing challenge to make clear what public affairs is about in the minds of students, employers, and the general public. The article concludes that the identity of an undergraduate public affairs education can be found in the meaning it provides to students seeking to make a civic difference.